2023
DOI: 10.35630/2023/13/5.505
|View full text |Cite
|
Sign up to set email alerts
|

X-Ray-Guided Endovascular Treatment for Critical Stenosis of a Solitary Internal Carotid Artery: A Clinical Case

Vyacheslav Mykhaylichenko,
Magomed Ahmadov,
Dmitry Parshin
et al.

Abstract: In this work, the authors present a clinical case of a 65 year-old man with a history of three acute cerebrovascular accidents similar to a transient ischemic attack and/or ischemic stroke with a minor neurological deficit with short-term weakness in the left or right limbs and loss of coordination. Carotid angiography showed that the blood supply to the brain was provided by a single internal carotid artery on the left and a potent collateral network on the same side. The patient underwent stenting of the int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…The results of large multicenter studies (NASCET, ECST, ACAS) showed the advantage of carotid endarterectomy (CEA) in asymptomatic and symptomatic patients with a high (70-99%) degree of stenosis of the internal carotid artery (ICA) compared with conservative treatment [12,13]. Multifocal atherosclerosis simultaneously affecting the carotid arteries, coronary vessels, renal and peripheral arteries is observed in 30-65% of cases.…”
Section: Introductionmentioning
confidence: 99%
“…The results of large multicenter studies (NASCET, ECST, ACAS) showed the advantage of carotid endarterectomy (CEA) in asymptomatic and symptomatic patients with a high (70-99%) degree of stenosis of the internal carotid artery (ICA) compared with conservative treatment [12,13]. Multifocal atherosclerosis simultaneously affecting the carotid arteries, coronary vessels, renal and peripheral arteries is observed in 30-65% of cases.…”
Section: Introductionmentioning
confidence: 99%